Slipping film excellent in slippage to aqueous emulsion
By forming a synovial film with two-layer structures of uneven particle layers composed of silicate particles and chloride polyolefin resin and an oil layer formed by dimethyl silicone oil on the inner surface of the storage container, the problem of insufficient sliding performance of aqueous emulsions in the prior art is solved, and efficient sliding performance and long-term use stability are achieved.
Patent Information
- Application Number
- JP2023175141
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, the coating film in the storage container has insufficient sliding performance on the aqueous emulsion, resulting in inconvenience in use.
A synovial film with two layers of structure is formed on the inner surface of the storage container: one is a particle uneven layer composed of silicate particles and a chloride polyolefin resin, and the other is an oil layer formed by dimethyl silicone oil. The adhesion energy between the two layers is higher than the adhesion energy between the oil layer and the aqueous emulsion.
The sliding performance of the aqueous emulsion on the inner surface of the storage container is significantly improved, and the performance of the synovial film can be maintained for a long time as the oil layer is firmly maintained in the uneven layer.
Smart Images

Figure 2025065737000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating film having excellent sliding properties for aqueous emulsions, and a storage container for aqueous emulsions. [Background technology]
[0002] In a storage container for an aqueous emulsion, it is desired to form a coating film that allows the aqueous emulsion to slide down quickly inside a tilted container so that a user can quickly drain the aqueous emulsion or can use it completely to the very end without leaving any behind in the container.
[0003] The inventors have previously proposed a coating composition containing an organic solvent-soluble fluororesin having a radically polymerizable reactive group, a one-terminus radically polymerizable polysiloxane, a graft copolymer obtained by copolymerizing a methacrylate monomer, a one-terminus reactive silicone oil, a curing agent, and an organic solvent. They have tested the sliding properties of the coating film produced by this composition against water and oil, and confirmed that the coating film has the required sliding properties (see Patent Document 1). The inventors have also previously proposed a sliding film in which a large amount of oil, such as vegetable oil or silicone oil, is distributed in the resin on the substrate, in which the volume ratio of oil near the surface is greater than the volume ratio of oil in the internal region, and multiple oil aggregates near the surface are exposed, each protruding from the surface, and the inventors have confirmed that the film has a predetermined sliding property (see Patent Document 2). Also, a coating composition for preventing snow adhesion has been disclosed that contains a thermoplastic resin, an acrylic silicone compound, silicone oil, and a solvent (see Patent Document 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-218462 A [Patent Document 2] JP 2018-184536 A [Patent Document 3] JP 2020-084127 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, even in the conventional coating films of Patent Documents 1 to 3, there is room for improvement in terms of the sliding properties of aqueous emulsions such as milky lotions.
[0006] The present invention has been made in consideration of the above problems, and aims to provide a sliding membrane that has excellent sliding properties for aqueous emulsions such as lotions and also has excellent durability, and a storage container for aqueous emulsions that has such a sliding membrane. [Means for solving the problem]
[0007] As a result of conducting many experiments on the sliding properties of aqueous emulsions, the inventors discovered that by forming a particle-convex layer on a substrate and then forming an oil layer on the surface of that layer, a sliding film with excellent sliding properties and durability against aqueous emulsions can be obtained, which led to the completion of the present invention.
[0008] That is, the sliding film having excellent sliding properties against the aqueous emulsion of the present invention is as follows: formed on the surface of the substrate, Component A: silica particles, and B component: chlorinated polyolefin resin, and a particle uneven layer formed by adding the particle uneven layer on the surface of the particle uneven layer. Component C: Kinematic viscosity at 25°C is 350m 2 / s exceeding 30,000 m 2 / s or less dimethyl silicone oil and an oil layer formed containing The sliding object is an aqueous emulsion, The silica particles include silica particles having at least a hydrophobic surface, the amount of the silica particles is more than 20 parts by mass and not more than 80 parts by mass relative to 100 parts by mass of the chlorinated polyolefin resin, The ratio of the coating amount of the particle concave-convex layer to the coating amount of the oil layer is within the range of 0.12 to 2.0.
[0009] The present invention is characterized in that the adhesion energy between the particle concave-convex layer and the oil layer is greater than the adhesion energy between the oil layer and the aqueous emulsion.
[0010] In the present invention, the weight of the particle uneven layer is 1.0 to 35.6 g / m 2 and the weight of the oil layer is 7.8 to 65.5 g / m 2 It is preferable that:
[0011] In the present invention, the silica particles preferably have an average primary particle size of 7 nm to 40 nm.
[0012] The storage container for an aqueous emulsion of the present invention is characterized in that the sliding membrane is formed on the inner surface of the storage container. Effect of the Invention
[0013] The composition of the sliding film of the present invention is a two-layer structure consisting of a particle uneven layer (including at least surface hydrophobic particles and chlorinated polyolefin resin) formed on a substrate and an oil layer (dimethyl silicone oil) formed on its surface, so that when the sliding layer contacts with aqueous emulsion, the layer of dimethyl silicone oil present on the surface of the sliding layer slides the aqueous emulsion, and exhibits excellent sliding properties against aqueous emulsion.In addition, the oil layer is firmly and stably held by the particle uneven layer, and the sliding properties against aqueous emulsion are maintained for a long time. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a diagram showing a schematic structure of the sliding film of the present invention formed on a substrate. [Diagram 2] 1 is an image showing the shape of a PET container used in an embodiment. [Diagram 3]This image can be used as a criterion for determining whether emulsion is slipping out of a PET container. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The following describes the embodiments of the present invention, but these are representative examples of the embodiments of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention. In the following description, "parts" means "parts by mass" and "%" means "% by mass" unless otherwise specified.
[0016] <Synovial membrane> The article having the sliding membrane of this embodiment is a storage container for aqueous emulsion, and a glass or resin substrate can be selected according to the application. Specific applications include storage of various cosmetics, detergents, edible products, etc. Referring to FIG. 1, the inner surface of the container that comes into contact with the aqueous emulsion is provided with a sliding membrane having a two-layer structure consisting of a particle uneven layer (component A, component B) formed on the surface of the substrate and an oil layer (component C) formed on the surface of the particle uneven layer. Therefore, the surface of the sliding membrane is wet with oil, and the oil is firmly held by the particle uneven layer. The sliding membrane of such a two-layer structure exhibits sliding properties for the aqueous emulsion on the inner surface of the container.
[0017] Aqueous emulsions are oil-in-water (O / W) emulsions, and a representative example is a cosmetic liquid such as a milky lotion. The viscosity of the aqueous emulsion is within the following range when measured for 300 seconds at the desired rotation speed (1, 12, 30, or 60 rpm) and temperature of 25°C using a B-type viscometer with an L4 spindle. Rotational speed (1 rpm): 9,000~24,000 mPa·s Rotational speed (12 rpm): 1,750 to 3,600 mPa·s Rotational speed (30 rpm): 800~ 4,500 mPa s Rotational speed (60 rpm): 700~ 1,200 mPa·s
[0018] For aqueous emulsions, the dispersion component of the surface free energy is 18.8–24.5 mJ / m 2and the polar component of the surface free energy is within the range of 3.1 to 9.2 mJ / m 2 The total surface free energy is within the range of 25.7 to 29.9 mJ / m 2 When the thickness is within the range, the sliding property of the sliding film is particularly effectively exhibited.
[0019] <Particle uneven layer> The particle-concave layer is formed by applying a coating material to the inner surface of the container. The coating material for the particle-concave layer contains silica particles (component A), a chlorinated polyolefin resin (component B), a solvent, and, if necessary, suitable additives.
[0020] Silica particles (component A) The silica particles include at least surface-hydrophobic silica particles. The surface-hydrophobic silica particles are formed by subjecting the surfaces of the silica particles to a hydrophobic treatment, and the hydrophobic treatment can be, for example, a method of coating the surfaces of the silica particles with polydimethylsiloxane.
[0021] In the particle uneven layer, a three-dimensional network structure is formed by laminating aggregates of silica particles on the surface of the substrate. The surface of the three-dimensional network structure has good affinity with dimethyl silicone oil, and the three-dimensional network structure has the effect of increasing the retention of dimethyl silicone oil. There is no limitation on the size of the silica particles, but if the average particle diameter of the primary particles is within the range of 7 to 40 nm, the retention of dimethyl silicone oil is higher. In particular, silica particles within the range of 7 to 30 nm and a specific surface area according to the BET method of 30 to 220 m are preferred. 2 / g is preferred.
[0022] Furthermore, two types of silica particles having different average primary particle sizes can be mixed in a weight ratio within the range of, for example, 20:80 to 80:20 to be used as the silica particles.
[0023] In the case of surface hydrophobic silica particles, commercially available products such as Aerosil (registered trademark) R972, R972CF, R972V, R974, R976, R976S, R9200 (imported product), RX50, NAX50, NX90G, NX90S, NX130, RX200, RX300, R812 (imported product), R812S (imported product), R8200 (imported product), RY50, RY51, NY50, NY50L, RY200S, RY200, RY200L, RY300, R202 (imported product), and R805 (imported product) (all manufactured by Nippon Aerosil Co., Ltd.) can be suitably used.
[0024] In addition, when surface-hydrophilic silica particles are mixed with surface-hydrophobic silica particles, the surface-hydrophilic silica particles may be preferably Aerosil (registered trademark) 50, 90G, 130, 200, 300, 380, etc., manufactured by the same company. The specific surface area of the surface-hydrophilic silica particles measured by the BET method is 35 to 410 m 2 The silica particles may be a mixture of surface-hydrophobic silica particles and surface-hydrophilic silica particles in a weight ratio of, for example, 20:80 to 80:20.
[0025] · Chlorinated polyolefin resin (B component) The chlorinated polyolefin resin is a component that is responsible for bonding between particles and between particles and the substrate in the particle-convex layer formed by coating. Although it depends on the use of the article to which the sliding film is applied, for example, in the case of a sliding film applied to a cosmetic container, a resin that is hard, transparent, and has excellent adhesion to the substrate, such as a chlorinated polyolefin resin, is preferable.
[0026] The polyolefin resin used as the material of the chlorinated polyolefin resin is preferably a polypropylene resin or a polyolefin resin obtained by copolymerizing propylene with an α-olefin (e.g., ethylene, butene, 3-methyl-1-butene, 3-methyl-1-heptene). More preferably, it is a propylene-based random copolymer, and even more preferably, it is a polypropylene, an ethylene-propylene copolymer, a propylene-butene copolymer, or an ethylene-propylene-butene copolymer.
[0027] The chlorinated polyolefin resin is a polyolefin in which at least a part of the hydrogen atoms is replaced with chlorine atoms, and the chlorine content (measurable according to JIS-K7229:1995) is preferably 10 to 40 mass%, more preferably 15 to 30 mass%. By setting the chlorine oil content within the above range, the polarity of the resin component can be adjusted within a certain range, so that the compatibility with other components in the coating material becomes good, and sufficient adhesion to the substrate can be obtained.
[0028] In order to obtain good compatibility and affinity with other components in the coating material, the weight-average molecular weight of the chlorinated polyolefin resin is preferably 50,000 to 200,000. If the weight-average molecular weight is 50,000 or more, the cohesive force of the resin component is sufficient, and the adhesion to the substrate is good. If the upper limit of the weight-average molecular weight is 200,000 or less, the compatibility with other components in the coating material is good, and sufficient adhesion to the substrate is obtained.
[0029] The weight average molecular weight can be determined by using a standard polystyrene calibration curve in a gel permeation chromatograph (GPC) device. The GPC measurement conditions are as follows: Equipment: HLC-8320GPC (Tosoh Corporation) Column: TSK-gel G-6000H XL , G-5000H XL , G-4000H XL , G-3000H XL , G-2000H XL (Manufactured by Tosoh Corporation) Eluent:THF Flow rate: 1mL / min Temperature: Pump oven, column oven 40℃ Injection volume: 100μL Standard material: Polystyrene EasiCal PS-1 (Agilent Technology)
[0030] As the chlorinated polyolefin resin, chlorinated polypropylene is preferred. In this embodiment, the chlorinated polyolefin resin may be a copolymer resin with other monomers. Examples of the copolymerizable monomers include acrylic monomers, acidic monomers, vinyl acetate monomers, and styrene monomers. Examples of the acidic monomers include maleic acid, maleic anhydride, fumaric acid, and (meth)acrylic acid. The chlorinated polyolefin resin may be replaced with a mixture of the chlorinated polyolefin resin and another resin, so long as the properties of the chlorinated polyolefin resin are exhibited.
[0031] ·solvent The solvent is not particularly limited as long as it can sufficiently dissolve the chlorinated polyolefin resin and disperse the silica particles. Examples of the solvent include ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanenone; esters such as methyl acetate, ethyl acetate, ethyl butyrate, and isopentyl acetate; alcohols such as methanol, ethanol, propanol, butanol, hexanol, and propylene glycol monomethyl ether; glycol esters such as ethylene glycol monoethyl ether acetate, butyl carbitol acetate, ethyl carbitol acetate, and propylene glycol monomethyl ether acetate; glycol ethers such as methyl carbitol, ethyl carbitol, butyl carbitol, methyl triglycol, propylene glycol monomethyl ether, 1-methoxy-2-propanol, propylene glycol monobutyl ether, and methyl methoxybutanol; amides such as formamide, acetamide, benzamide, and N,N-dimethylformamide; hydrocarbons such as normal hexane, cyclohexane, ethyl cyclohexane, isooctane, normal decane, and normal pentane; aromatic hydrocarbons such as benzene, toluene, and xylene; and halides thereof. One or more solvents selected from these can be used by mixing them appropriately. In particular, by using methyl ethyl ketone, isopropanol, butyl acetate, etc., which volatilize in air at about room temperature, a coating material capable of easily forming a sliding film can be obtained.
[0032] In addition to the above-mentioned components, the coating material for the particle uneven layer may contain various additives known per se, such as plasticizers, dispersants, antioxidants, UV absorbers, fillers, and leveling agents (to prevent repelling during spray coating), depending on the application of the container. Furthermore, in applications where transparency is not required, colorants such as pigments and dyes can also be added. Furthermore, it is also possible to add crystalline additives (inorganic oxides such as titanium oxide and various waxes). If necessary, a curing agent can also be added.
[0033] In preparing the coating material for the particle uneven layer, the ratio of silica particles (component A) and chlorinated polyolefin resin (component B) is not particularly limited, but the silica particles can be more than 20 parts by mass and 80 parts by mass or less, and particularly preferably 70 to 80 parts by mass, per 100 parts by mass of the chlorinated polyolefin resin in the particle uneven layer after coating and drying. Hereinafter, the unit of amount may be expressed as phr [Parts per Hundred parts of Resin (or Rubber)].
[0034] If the ratio of silica particles is too high, the binding power of the chlorinated polyolefin resin after heating and drying may be insufficient. Also, the thixotropy may increase, making the coating more prone to unevenness. On the other hand, if the ratio of silica particles is too low, the uneven structure may become insufficient, reducing the oil layer retention.
[0035] For the particle-convex layer, the dispersion component of the surface free energy is 27.4 to 38.6 mJ / m 2 The polar component of the surface free energy is in the range of 0 to 6.6 mJ / m 2 The total surface free energy is within the range of 33.3 to 38.6 mJ / m 2 When the thickness is within the range, the sliding property of the sliding film is particularly effectively exhibited.
[0036] The amount of coating material for the particle uneven layer is not particularly limited, but is preferably 1.0 to 35.6 g / m2 in terms of weight per area after drying. 2The weight after drying can be calculated from the difference between the weight of the substrate only before coating and the total weight after coating and drying.
[0037] The coating material for the particle uneven layer can be applied to the surface of the substrate in the container, and then the solvent can be evaporated by drying through heating or the like to form a sliding film. Examples of substrates to which the coating material can be applied include glass and resin. Examples of resins that can be used include polyester (polyethylene terephthalate resin, etc.), acrylic resin, and polycarbonate resin. For example, the dispersion component of the surface free energy of polyester is 43.2 mJ / m 2 and the polar component of the surface free energy is 4.2 mJ / m 2 The total surface free energy is 47.4 mJ / m 2 It is.
[0038] The coating material can be applied to the surface of the substrate by any conventional coating method such as doctor blade method, bar coating method, dipping method, air spray method, roller brush method, roller coater method, etc. As for the drying method, in addition to drying by heating, the substrate to which the coating material is applied can be left in an atmosphere at about room temperature until the solvent is sufficiently evaporated to form a sliding film.
[0039] <Oil layer> The oil layer is formed by applying dimethyl silicone oil (component C) to the surface of the particle uneven layer after its formation. The dimethyl silicone oil is held in place by the uneven surface of the particle uneven layer, so the oil layer maintains its sliding properties for a long time. Dimethyl silicone oil has a dimethyl polysiloxane structure and has a kinetic viscosity of 350 m at 25°C. 2 / s, exceeding 30,000 m 2 It is preferable that the range is less than 1,000 to 10,000 m / s, and particularly, 2 It is preferable that the range is / s.
[0040] Dimethyl silicone oil forms an oil film on the surface of the sliding film, enhancing the property of the aqueous emulsion moving smoothly. Therefore, it is preferable that the surface free energy of the oil itself is smaller than the surface free energy of the aqueous emulsion. The total value of the surface free energy of the dimethyl silicone oil is 21.0 to 23.0 mJ / m 2 When the thickness is within the range, the sliding property of the sliding film is particularly effectively exhibited.
[0041] The dimethyl silicone oil may be a mixture of two types of dimethyl silicone oil with different kinetic viscosities, for example, a mixture in a weight ratio of 20:80 to 80:20.
[0042] The amount of dimethyl silicone oil applied for the oil layer is not limited, but is generally 7.8 to 65.5 g / m 2 If the weight of the oil is too small, it may not be possible to ensure good sliding properties on the inner surface of the container, whereas if the weight of the oil is too large, it may not be retained on the wall of the container and may run off.
[0043] The dimethyl silicone oil can be applied by any conventional coating method such as a doctor blade method, a bar coating method, a dipping method, an air spray method, a roller brush method, or a roller coater method.
[0044] The ratio of the coating amount of the particle uneven layer to the coating amount of the oil layer is preferably in the range of 0.12 to 2.0. If the coating amount ratio exceeds 2.0, the ratio of the oil layer to the particle uneven layer decreases, and sufficient slippage may not be obtained. Also, if the coating amount ratio is less than 0.12, the ratio of the particle uneven layer to the oil layer decreases, and the oil layer may not be sufficiently maintained.
[0045] In this way, the aqueous emulsion that comes into contact with the oil layer on the sliding film surface slides down the surface due to the difference in surface free energy between the aqueous emulsion and the dimethyl silicone oil. EXAMPLES
[0046] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the contents of these examples.
[0047] Physical properties, etc. are measured by the following methods unless otherwise specified. [Mixing ratio and coating amount of particle uneven layer] The compounding ratio of the particle concavo-convex layer, that is, the compounding ratio of component A and component B of the silica particles to 100 parts by mass of the chlorinated polyolefin resin, is calculated based on the amount of coating after drying (or on a non-volatile content basis). The coating amount of the particle uneven layer is the weight of the particle uneven layer per coating area, and is a calculated value. First, the amount of coating film used after coating and drying is calculated from the difference in the container weight before coating and after coating and drying. This is divided by the coating area in the container to obtain the coating amount (g / m2). 2 )
[0048] [Amount of oil applied] Oil layer application amount (g / m 2 ) is also the weight of the oil layer per coated area, and is calculated by dividing the difference in the container weight before and after coating by the coated area, as described above.
[0049] The container (substrate), sliding film (particle uneven layer and oil layer), and contents (subject to sliding) used in the examples are as follows.
[0050] <Container> The container is made of polyethylene terephthalate (PET). The coating area of the PET container is calculated by assuming the inside of the container to be cylindrical (inner diameter 36.72 mm, height 102.5 mm) and adding up the areas of the bottom and sides (1.29 x 10 -2 m 2 ) is used.
[0051] <Synovial membrane> (particle uneven layer) (1) Particles Hydrophobic Silica Particles Hydrophilic Silica Particles Silicone resin particles (silicone resin powder) (2) Chlorinated polyolefin resin Chlorinated polyolefin: Sakuramiya Chemical Co., Ltd. "CA-PL01" (contains organic solvents) For comparison, a vinyl chloride / vinyl acetate resin and a fluorine-based copolymer resin (a resin containing a polyfluoroalkyl methacrylate resin) were used. Vinyl chloride acrylic resin: "KW" manufactured by Sakuramiya Chemical Co., Ltd. (contains organic solvents) Fluorine-based copolymer resin: Commercially available As a solvent for chlorinated polyolefin resin, ketones, esters, alcohols, and hydrocarbons were used according to the resin. If the container was made of resin, a solvent that could avoid clouding due to crystallization of the resin (e.g., transparent polyester resin) was selected and used. These particles and chlorinated polyolefin resin were mixed and stirred to prepare a coating material with the particles dispersed, and a specified amount of coating material was evenly applied to the inner surface of the container and dried to form a particle-convex layer. The coating method for the inner surface of the PET container was "spray" or "flow coating." In both coating methods, the coating was dried after coating. The drying temperature and drying time were 100°C and 30 seconds. However, if sufficient drying time can be secured, it is also possible to form a coating film by drying at room temperature at 25°C. Table 1 shows a list of the particle uneven layer.
[0052] [Table 1]
[0053] The surface free energy of the particle uneven layer in Table 1 is based on the typical Kaelble and Uy theoretical formula. First, a coating film consisting of only the particle uneven layer is formed on a glass slide, and the contact angle of a 10 μL droplet of two reagents (selected from water, diiodomethane, formamide, 1-bromonaphthalene, n-hexadecane, decane, and heptane) on the coating film is measured using a contact angle meter Drop Master DMs-401 (Kyowa Interface Science Co., Ltd.). These contact angle measurements are applied to the theoretical formula to calculate the dispersion component and polar component of the surface free energy, and the sum of these is taken as the surface free energy of the particle uneven layer.
[0054] (Oil layer) A silicone oil with a dimethylpolysiloxane structure is used. For comparison, a side-chain / fluoroalkyl-modified non-reactive silicone oil other than that having a dimethylpolysiloxane structure is used. In addition, a silicone oil film was formed on a slide glass, the contact angle of a 10 μL droplet of a reagent (water, diiodomethane) to the oil film was measured, and the surface free energy of the silicone oil was calculated. A list of these silicone oils is shown in Table 2.
[0055] [Table 2]
[0056] The sliding film of the example was formed inside a PET container by combining the above-mentioned particle uneven layer and oil layer in the compounding ratio shown in Tables 4 to 8. The oil layer was applied to the surface of the particle uneven layer by "spraying" or "flow coating".
[0057] <Contents> The prepared slide-off membrane was subjected to a slide-off durability test using emulsion. The physical properties of the commercially available emulsions used in the tests are shown in Table 3.
[0058] [Table 3]
[0059] Regarding the viscosity of the emulsion, since the viscosity of "mayonnaise" according to the literature is 8000 mPa s, the viscosity of "Kewpie Half (registered trademark)" was measured using a B-type viscometer with various settings of the rotation speed to confirm the rotation speed condition under which a viscosity value equivalent to the value in the literature was obtained, and an actual measured value of 7670 mPa s was obtained at 30 rpm. Based on this, the rotation speed condition for measuring the viscosity of the emulsion was set to 30 rpm. To measure the viscosity of the emulsion, a 20 g vial (SV-50A) (manufactured by Nichiden Rika Glass Co., Ltd.) was used, and an L4 spindle (diameter 3.2 mm) was placed at the center of the vial (inner diameter 26.5 mm) with an inner gap of 11.65 mm between the spindle and the inner wall of the vial.
[0060] The method for measuring the surface free energy of the emulsion was the same as that for measuring the surface free energy described above. The emulsion was spread on a slide glass to form a film, and the contact angles of 10 μL droplets of two reagents (diiodomethane and n-hexadecane) to the emulsion film were measured using a contact angle meter Drop Master DMs-401 (Kyowa Interface Science Co., Ltd.), and the surface free energy of the emulsion was calculated using the measured contact angles.
[0061] As shown below, the sliding film of this example has a viscosity of 810 to 4070 mPa s and a surface free energy of 25.7 to 29.9 mJ / m 2 It exhibits excellent slip resistance against emulsions.
[0062] [Slip-down durability test] Fill the container with the coating with 10 g of emulsion 1 to 6 in Table 3, and seal it with an inner stopper and a cap. Repeatedly turn the container upside down and upright as follows, and visually evaluate the sliding property (removal performance) of the coating against the emulsion after each inversion. 1st time: upright → inverted (record the date and time of inversion: 1st time start date and time) After the first inversion, leave the container in the inverted position until there is no more emulsion adhering to the inside of the container (bottom and sides) and it is determined that the emulsion has slid down to the cap side. When it is visually confirmed that the emulsion has slid down, begin the second inversion. 2nd time: Inverted → Upright (record the date and time when it was upright: start date and time of the 2nd time) Leave the container in the upright position until there is no more emulsion adhering to the inside of the container (shoulder and sides) and it is determined that the emulsion has slid to the bottom. When it is visually confirmed that the emulsion has slid down, begin the third inversion. 3rd time (and every odd number of times thereafter): upright → inverted (same as 1st time) 4th time (and every even number of times thereafter): Inverted → Upright (same as 2nd time)
[0063] The quality of the sliding property of the inner surface of the container (easily or not easily adhered to) is affected not only by the difference in the material of the inner surface of the container, but also by the difference in the shape of the container (e.g., the shape of the shoulder part, the shape of the bottom surface, etc.). For this reason, the shape of the PET container used in the examples is shown in Figure 2.
[0064] The criteria for visually checking whether lotion has slid down will be explained with reference to the images in FIG. 3. The image in the upper left of FIG. 3 is the appearance of the PET container of Example 3, and is an image that serves as a guide for determining whether lotion 1 has slid down. The image in the upper right of FIG. 3 is the appearance of the PET container of Comparative Example 15, and is an image that serves as a guide for determining whether lotion 1 has not slid down. The image in the lower left of FIG. 3 is the appearance of the PET container of Example 71, and is an image that serves as a guide for determining whether lotion 5 has slid down. The image in the lower right of FIG. 3 is the appearance of the PET container of Comparative Example 71, and is an image that serves as a guide for determining whether lotion 5 has not slid down. These images are used as a guide to determine whether each lotion has slid down.
[0065] "Evaluation method for slip resistance" We will now explain how to evaluate how long a container can maintain the emulsion's ability to slide off (slide durability). First, we will explain how to use a commercially available emulsion (contained in a 60 mL container). Assuming that the amount used each time is about the area of a 100 yen coin (approximately 2.5 mL per use), one commercially available emulsion can be used 24 times. In other words, if the emulsion's ability to slide off is maintained even after the 24th use, the appearance (transparency) of the container will be well maintained, and the emulsion container can be evaluated as having slide durability. The action of using a commercially available lotion once involves lifting the container from the upright position, tilting it (to dispense the lotion), and then returning it to the upright position, which is an "upright → inverted → upright" action. Therefore, repeating the inversion action in the above test up to 48 times is equivalent to the number of uses of one commercially available lotion (24 times). Therefore, by repeating the inversion work up to 100 times, which is more than twice the number of times, and if there is no lotion adhering (residual) to the inner surface of the container by the start of the 100th inversion and the lotion can be visually confirmed to be sliding down, it can be determined that "slide durability (durability of lotion removal) is present." After the 100th inversion, the evaluation of slide durability itself was continued until the start of the 200th inversion, which is twice the number of times, and the evaluation was terminated at the same time as the start of the 200th inversion.
[0066] In the sliding durability test, in order to properly evaluate the sliding durability of lotion and also the sliding speed of lotion, we decided to use the "number of times per 12 hours (including holidays)". In general, it is assumed that commercially available lotions are used twice a day (every 12 hours). Therefore, it is desirable that after the container is inverted, at the longest, 12 hours later, there is almost no lotion remaining on the inner surface of the container and the lotion can be visually confirmed to have slid down. In other words, in the above sliding durability test, if the number of inversions per 12 hours is 1 or more, the evaluation of sliding durability is high. Therefore, we decided to introduce the "number of times per 12 hours" as a numerical value indicating the degree of sliding durability. However, considering that lotion is often left unused on holidays, etc., the criterion for judging whether there is sliding durability is 0.71 times (≒ 1 time x 5 days / 7 days) or more per 12 hours (including holidays). For example, if the reversal operation has reached its 200th time (reversal count: 199 times) and 54 days have passed since then, the number of times per 12 hours (including holidays) is calculated as 199 times / (54 days x 2) = 1.84 times.
[0067] After inversion, the container was left alone until it was determined that the lotion had slid off, so if the lotion continued to adhere indefinitely, the evaluation was terminated after a certain period of time had passed. In this case, the number of inversions per 12 hours was calculated from the number of inversions at the last inversion and the number of days that had passed. For example, if the number of inversions at the last inversion was 37 and the number of days that had passed was 28, the number of inversions per 12 hours (including holidays) would be calculated as 37 times / (28 days x 2) = 0.66 times.
[0068] The degree of slip resistance was evaluated according to the following criteria: If the number of inversions per 12 hours (including holidays) was 0.71 or more (ratings A to C), there was no practical problem. AA: 1.5 or more times per 12 hours (including holidays) A: The number of times per 12 hours (including holidays) is 1.0 or more and less than 1.5 B: Number of incidents per 12 hours (including holidays) is 0.71 or more and less than 1.0 C: The number of incidents per 12 hours (including holidays) is less than 0.71 Furthermore, since the amount used per application and the method of use vary depending on the type of lotion and the user, the evaluation criteria here are set merely as a guideline.
[0069] The evaluation results using lotion 1 are shown in Tables 4 and 5.
[0070] [Table 4]
[0071] [Table 5]
[0072] An "upward arrow" in the table indicates that the value is the same as in the upper column. In the "Number of times" column in the table, 199 times indicates that the evaluation ended at the same time as the start of the next 200th time. In Example 12, two types of silica particles, one with a hydrophobic surface and one with a hydrophilic surface, were mixed in a mass ratio of 1:1. Moreover, in Examples 13 and 14, two types of silica particles having different average particle sizes (specific surface areas) and different surface hydrophobicity were used in a 1:1 mass ratio. In Comparative Examples 11 to 13, surface-hydrophobic silicone resin particles with an average particle size of 2 μm were used instead of silica particles. In Comparative Example 14, surface-hydrophobic silicone resin particles with an average particle size of 0.7 μm were used instead of silica particles. All of the silicone resin powders are spherical powders of methyltrimethoxysilane polymers.
[0073] The evaluation results using lotion 2 are shown in Tables 6 and 7.
[0074] [Table 6]
[0075] [Table 7]
[0076] In Comparative Examples 21 to 28, acrylic chloride acetate was used instead of chlorinated polyolefin, and in Comparative Examples 29 to 31, fluorine-based copolymer resin was used instead of chlorinated polyolefin. In particular, in Comparative Examples 27, 28, 30, and 31, fluoroalkyl-modified silicone oil was used instead of dimethyl silicone oil. In Comparative Examples 33 and 34, hydrophilic silica particles are used instead of hydrophobic silica particles.
[0077] The evaluation results using emulsions 3 to 6 are shown in Table 8.
[0078] [Table 8]
[0079] In Examples 82 and 83, the oil layer was formed using two types of dimethyl silicone oils having different kinetic viscosities in a mass ratio of 1:1.
[0080] According to the test results using these various emulsions, the emulsions having a particle concavo-convex layer formed of at least surface-hydrophobic silica particles and chlorinated polyolefin resin and a kinetic viscosity of 350 m at 25°C are 2 / s exceeding 30,000 m 2 / s, wherein the amount of silica particles is more than 20 parts by mass and not more than 80 parts by mass per 100 parts by mass of chlorinated polyolefin resin, and the ratio of the amount of application of the particle uneven layer to the amount of application of the oil layer is within the range of 0.12 or more and 2.0 or less.By forming a sliding film on the inner surface of a PET container, it can be seen that the sliding property of the lotion is maintained for a long time, and sliding durability sufficient for practical use is obtained.
[0081] <Evaluation of sliding durability of sliding film based on adhesion energy> The inventors further attempted to evaluate the sliding durability based on the adhesion energy, predicting that a sliding film with excellent sliding durability would be obtained when the adhesion energy between the particle uneven layer and the oil layer is greater than the adhesion energy between the oil layer and the aqueous emulsion.
[0082] "How to calculate adhesion energy" In general, the interfacial free energy (γLS) between a coating film and an emulsion is expressed by equation (1). γLS=γL+γS-2√(γLd·γSd) ···(1) where γL is the surface free energy of the emulsion, (Hereafter, unless otherwise specified, it refers to the sum of the variance component and the polarity component.) γS: Surface free energy of the coating film, γLd: surface free energy of emulsion (dispersion component), γSd: Surface free energy of the coating film (dispersion component). is based on the theoretical formula of Fowkes. Fowkes hypothesized that only dispersion forces act between nonpolar molecules and between nonpolar and polar molecules, and that the interaction is expressed as the geometric mean of the surface tensions of each, and proposed the theoretical formula (1) for the interfacial tension between solids and liquids in 1964. Meanwhile, Young's equation is expressed as "γS = γL cosθ + γLS" (θ is the contact angle of the emulsion with the coating film). Also, the adhesion energy (WLS) is expressed by Dupre's equation "γL + γS = WLS + γLS" in formula (2). WLS = γL + γS - γLS (2) In this way, the adhesion energy of the emulsion to the coating film is expressed as "γL + γS - γLS." In other words, the surface free energies γL, γS, γLd, and γSd in formula (1) can be obtained using the theoretical formula of Kaelble and Uy, which is the theoretical formula for surface free energy, and the measured value of the contact angle of the reagent (10 μL droplet) using the contact angle meter mentioned in the explanation of the surface free energy in Table 1. Then, γLS can be obtained from formula (1), and the adhesion energy expressed as WLS can be obtained from formula (2).
[0083] Here, for each type of emulsion, the adhesion energy of the emulsion to the oil layer (adhesion energy 1) and the adhesion energy of the oil layer to the particle uneven layer (adhesion energy 2) were calculated. In addition, the adhesion energy of the particle uneven layer to the substrate (adhesion energy 3) was also calculated. These adhesion energies 1 to 3 can be calculated using the measured values of surface free energy shown in Tables 1 to 3.
[0084] The ratio of the two adhesion energies 1 and 2 is theoretically expressed as follows: Adhesion energy 2 / Adhesion energy 1 = √(dispersion component of surface free energy of particle uneven layer / dispersion component of surface free energy of emulsion) and is determined by the dispersion component of the surface free energy of the particle concave-convex layer and the dispersion component of the surface free energy of the emulsion, regardless of the oil layer. Tables 9 and 10 show the calculation results of adhesion energies 1 to 3.
[0085] [Table 9]
[0086] [Table 10]
[0087] In Examples 1 to 7 and 9 to 14 of emulsion 1, the silica particles constituting the particle concave-convex layer and their blending ratio were changed in several ways, and in the configuration of each example, "adhesion energy 1 < adhesion energy 2 < adhesion energy 3" was established, and the slippage durability was good. This was also the case for the other emulsions (2 to 5), and the difference range of "(adhesion energy 2) - (adhesion energy 1)" in the examples of emulsions 1 to 5 was 3.19 to 17.06 mJ / m 2 It is. In addition, in comparison examples 29 to 31, 52, and 62 for emulsion 2, emulsion 3, and emulsion 4, when the particle uneven layer was formed from a fluorine-based copolymer resin and hydrophilic silica, adhesion energy 1 was greater than adhesion energy 2, and the difference between "(adhesion energy 2) - (adhesion energy 1)" was negative. These results show that there is a correlation between the adhesion energy 2 between the particle uneven layer and the oil layer being greater than the adhesion energy 1 between the oil layer and the aqueous emulsion, and good slip resistance test results.
Claims
1. A slip film formed on the surface of a substrate, Component A: silica particles, and B component: chlorinated polyolefin resin, and a particle uneven layer formed by adding the particle uneven layer on the surface of the particle uneven layer. Component C: kinematic viscosity at 25°C of 350 m 2 / s exceeding 30,000m 2 Dimethyl silicone oil in the range of less than 1 / s and an oil layer formed containing The sliding object is an aqueous emulsion, The silica particles include silica particles having at least a hydrophobic surface, the amount of the silica particles is more than 20 parts by mass and not more than 80 parts by mass relative to 100 parts by mass of the chlorinated polyolefin resin, A sliding film, characterized in that the ratio of the coating amount of the particle uneven layer to the coating amount of the oil layer is within the range of 0.12 to 2.
0.
2. 2. The sliding film of claim 1, wherein the adhesion energy between the particle-convex layer and the oil layer is greater than the adhesion energy between the oil layer and the aqueous emulsion.
3. The weight of the particle uneven layer is 1.0 to 35.6 g / m 2 and the weight of the oil layer is 7.8 to 65.5 g / m 2 2. The method according to claim 1, characterized in that:
4. 2. The method according to claim 1, wherein the silica particles have an average primary particle size of 7 nm to 40 nm.
5. A storage container for aqueous emulsions, characterized in that the sliding membrane according to any one of claims 1 to 4 is formed on the inner surface thereof.
Citation Information
Patent Citations
Falling film
JP2018184536A
Sliding-down agent and article coated with coating thereof
JP2019218462A
Coating agent, coating film and article using the same, and snow accretion prevention method of article surface
JP2020084127A